Preclusão hierárquica - Almeida, Flávio Renato Correia de (2018)
The presente study aims do analyse preclusion, its species and, in particular, the preclusion resulting from requirement subjecting the judge of first instance decisions of the court to which it is subject, as well as the higher courts